The German classics of the nineteenth and twentieth centuries: masterpieces of German literature translated into English - Francke, Kuno (German Publication Society, 1913)
Vol. 1-2. Goethe.- Vol. 3. Schiller.- Vol. 4. Jean Paul; Wilhelm von Humboldt; A.W. Schlegel; Friedrich Schlegel; Novalis; Friedrich Hölderlin; Ludwig Tieck; Heinrich von Kleist.- Vol. 5. Friedrich Schleiermacher; J.G. Fichte; F.W.J. von Schelling; L.A. von Arnim; Clemens Brentano; Jacob Grimm; Wilhelm Grimm; E.M. Arndt; Theodor Körner; M.G. von Schenkendorf; Ludwig Uhland; Joseph von Eichendorff; Adalbert von Chamisso; E.T.A. Hoffmann; Friedrich Baron de la Motte-Fouqué; Wilhelm Hauff; Friedrich Rückert; August von Platen-Hallermund.- Vol. 6. Heinrich Heine; Franz Grillparzer; Ludwig van Beethoven.- Vol. 7. G.W.F. Hegel; Bettina von Arnim; K.L. Immermann; K.F. Gutzkow; Anastasius Grün, Nikolaus Lenau; Eduard Mörike; A.E. von Droste-Hülshoff; Ferdinand Freiligrath; Moritz Graf von Strachwitz; Emanuel Geibol; Georg Herwegh.- Vol. 8. Berthold Auerbach; Jeremias Gotthelf; Fritz Reuter; Adalbert Stifter; Wilhelm Heinrich Riehl.- Vol. 9. Friedrich Hebbel; Otto Ludwig.- Vol. 10. Prince Otto von Bismarck; Count Helmuth von Moltke; Ferdinand Lassalle.- Vol. 11. Friedrich Spielhagen; Theodor Storm; Wilhelm Raabe.- Vol. 12. Gustav Freytag; Theodor Fontane.- Vol. 13. Paul Heyse; J.V. von Scheffel; Marie von Ebner-Eschenbach; Heinrich Seidel.- Vol. 14. Gottfried Keller; C.F. Meyer; J.V. Widmann; Carl Spitteler.- Vol. 15. Arthur Schopenhauer; Richard Wagner; Friedrich Nietzsche; Emperor William II.- Vol. 16. Adolf Wilbrandt; Ludwig Anzengruber; Peter Rosegger; Karl Schönherr.- Vol. 17. Ernst von Wildenbruch; Hermann Sudermann; Gustav Frenssen; Wilhelm von Polenz; Ludwig Fulda; Hugo Hofmannsthal; Herhart Hauptmann; Ferdinand von Saar; Detlev von Liliencron; Prince Emil von Schönaich-Carolath; Gustav Falke; Isolde Kurz; Richard Dehmel; Arno Holz; O.J. Bierbaum; Stefan George; Lulu von Strauss und Torney; Börries von Münchhausen; Rainer Maria Rilke; Hermann Hesse; Agnes Miegel; Ricarda Huchae.- Vol. 19. Helene Böhlau; Clara Viebig; Eduard von Keyserling; Thomas Mann; Ludwig Thoma; Rudolf Hans Bartsch; Emil Strauss; Hermann Hesse; Ernst Zahn; Jakob Schaffner.- Vol. 20. Jakob Wassermann; Bernhard Kellermann; Max Halbe; Hugo von Hofmannsthal; Arthur Schnitzler; Frank Wedekind; Ernst Hardt.